2021
DOI: 10.1002/nop2.838
|View full text |Cite
|
Sign up to set email alerts
|

Effect of prenatal aerobic exercises on maternal and neonatal outcomes: A systematic review and meta‐analysis

Abstract: Pregnancy is among the most sensitive and important stages in the life of parents, and childbirth is an important event in a woman's life. The duration of labour varies in different women and is affected by factors such as age, parity, foetal size and maternal weight (Chen et al., 2018).A prolonged first stage of labour entails complications such as compressed foetal head in the birth canal, lower neonatal Apgar score and foetal death (Allen et al., 2007). A prolonged second stage of labour is associated with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
8
0
3

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 48 publications
4
8
0
3
Order By: Relevance
“…However, both studies also mentioned that physical activity during pregnancy did not adversely affect the gestation period and cause premature delivery. The results of the current study on birth weight are also consistent with studies by da Silva et al [25], Veisy et al [33], and Du et al [23], where there was no significant evidence observed in both groups that show the effect of physical exercise on neonatal birth weight. Evidence on the roles of exercise in maintaining an optimum gestational age and birth weight at delivery is limited and inconclusive in most studies, hence makes it difficult to draw a clear conclusion on the matter.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…However, both studies also mentioned that physical activity during pregnancy did not adversely affect the gestation period and cause premature delivery. The results of the current study on birth weight are also consistent with studies by da Silva et al [25], Veisy et al [33], and Du et al [23], where there was no significant evidence observed in both groups that show the effect of physical exercise on neonatal birth weight. Evidence on the roles of exercise in maintaining an optimum gestational age and birth weight at delivery is limited and inconclusive in most studies, hence makes it difficult to draw a clear conclusion on the matter.…”
Section: Discussionsupporting
confidence: 92%
“…The present study does not found any significant results for gestational age and birth weight between both groups (P=0.83 and P=0.29, respectively). The results were consistent with other meta-analyses on gestational age at delivery conducted by Gema Sanabria-Martínez et al [32] and Veisy et al [33]. Both authors found no significant differences in terms of gestational age at delivery for the exercise intervention group and control group with P=0.284 and P=0.72 respectively.…”
Section: Discussionsupporting
confidence: 91%
“…In addition, regarding the advantages of Pilates in prenatal period; majority of the women (82.5%) stated that it helped them have a more flexible and active pregnancy. A systematic review and meta-analysis study by Veisy et al showed that prenatal exercise can reduce the frequency of caesarean section (22). In this study, majority of the women who had had vaginal delivery (52.5%) indicated that Pilates facilitated vaginal delivery.…”
Section: Discussionmentioning
confidence: 49%
“…The prenatal maternal body mass index (BMI) was calculated using the following formula: body weight (kg)/(body height (m)) 2 . Weight changes during pregnancy were generated from participant medical files and were computed using the difference between the weight measured at the most recent pregnancy medical check-up during pregnancy and the weight before gestation.…”
Section: Anthropometric Datamentioning
confidence: 99%
“…The benefits associated with physical activity during pregnancy for both maternal and new-born health are supported by research [ 1 , 2 , 3 , 4 ]. For example, regular physical activity during pregnancy has been linked to reduced risk of weight gain [ 5 ], hypertension [ 6 ], diabetes [ 5 , 6 ], back pain [ 7 ], mood disorders [ 8 , 9 ], large for gestational age [ 3 ], premature birth [ 3 ], and caesarean sections [ 2 ]. In 2020, the World Health Organization (WHO) updated physical activity and sedentary behaviour guidelines [ 10 ].…”
Section: Introductionmentioning
confidence: 99%